2016
DOI: 10.1111/medu.13208
|View full text |Cite
|
Sign up to set email alerts
|

Imperfect practice makes perfect: error management training improves transfer of learning

Abstract: The provision of error management instructions during simulation-based training improves the transfer of learning to the clinical setting compared with error avoidance instructions. Rather than teaching to avoid errors, the use of errors for learning should be explored further in medical education theory and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 40 publications
1
33
0
3
Order By: Relevance
“…For example, the use of errormanagement instructions may add no or little additional cost to training but can result in large improvements in transfer of learning. 8 Conversely, large cost savings may lead to a decrement in educational effectiveness that might or might not be acceptable depending on the magnitude and nature of what is being lost. To use a hypothetical example, if we can get 80% of the educational effectiveness for 40% of the cost, that would probably be an acceptable exchange.…”
Section: Martin G Tolsgaard 1 and David A Cookmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the use of errormanagement instructions may add no or little additional cost to training but can result in large improvements in transfer of learning. 8 Conversely, large cost savings may lead to a decrement in educational effectiveness that might or might not be acceptable depending on the magnitude and nature of what is being lost. To use a hypothetical example, if we can get 80% of the educational effectiveness for 40% of the cost, that would probably be an acceptable exchange.…”
Section: Martin G Tolsgaard 1 and David A Cookmentioning
confidence: 99%
“…A small increase in cost may be associated with large improvements in learning. For example, the use of error‐management instructions may add no or little additional cost to training but can result in large improvements in transfer of learning . Conversely, large cost savings may lead to a decrement in educational effectiveness that might or might not be acceptable depending on the magnitude and nature of what is being lost.…”
mentioning
confidence: 99%
“…Over the past decade, ultrasound simulators have been used increasingly as an adjunct to clinical training in the field of obstetrics and gynecology. Studies have shown that simulation‐based ultrasound training leads to sustained improvement in clinical performance, including improved diagnostic accuracy, reduced need for supervised practice and decreased patient discomfort. In addition to being a valuable tool for training, ultrasound simulators can also be used for the assessment of trainee competence.…”
Section: Introductionmentioning
confidence: 99%
“…In a Danish study, Dyre et al. investigated a contrasting approach – encouraging students to make mistakes . They randomised medical students learning fetal ultrasound to either error management training (EMT) or error avoidance training (EAT).…”
mentioning
confidence: 99%